THE EFFECT OF CARBON BLACK ON THE MECHANICAL PROPERTIES OF ASPHALT MIXTURES - Ahmedzade, Perviz; Alatas, Taner; Geckil, Tacettin (Yildiz Technical Univ, 2007)
The effect of carbon black used as a filler on the mechanical properties of asphalt mixtures was investigated. The asphalt mixtures in which carbon black and limestone fillers that have the same aggregate gradation were prepared and optimum bitumen content was determined by Marshall stability test. Mechanical characteristics of the carbon black and control mixtures were evaluated with Marshall stability, indirect tensile stiffness modulus, creep stiffness and indirect tensile strength tests. From these tests values it is clear that the best results were obtained from mixtures with carbon black filler. The results of investigation show that carbon black improves the mechanical properties of asphalt mixtures.
Keywords: Asphalt concrete; carbon black; stiffness modulus; creep stiffness; indirect tensile strength